2016
DOI: 10.1016/j.rboe.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty with subvastus approach in patient with chronic post-traumatic patellar dislocation

Abstract: Chronic lateral dislocation of the patella is a rare condition and acquired causes are usually secondary to knee trauma. The neglected chronic dislocation leads to progressive genu valgum and external tibial torsion deformities with subsequent gonarthrosis, which becomes painful and debilitating. There is no consensus regarding treatment of these patients, but total knee arthroplasty (TKA) is a useful therapy in cases of painful symptomatic gonarthrosis. Few reports have shown that subvastus approach and later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“… 2 , 18 In et al 2 observed one case of patellar tilt in their series with this surgical approach. In turn, Junqueira et al 14 reported a good result in their published case. However, those authors did not present an axial patellar radiograph.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“… 2 , 18 In et al 2 observed one case of patellar tilt in their series with this surgical approach. In turn, Junqueira et al 14 reported a good result in their published case. However, those authors did not present an axial patellar radiograph.…”
Section: Discussionmentioning
confidence: 81%
“… 2 The literature that correlates TKA and osteoarthritis with the presence of permanent patellar dislocation is scarce. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 In this literature review, the authors observed that, among the various difficulties, surgical approach is one that deserves attention, as there is no consensus regarding which is the best option. This study is aimed at presenting two cases of permanent patellar dislocation in patients with osteoarthritis who underwent TKA.…”
Section: Introductionmentioning
confidence: 99%
“…One potential disadvantage regarding the use of a medial parapatellar approach combined with a lateral release is the potential devascularization of the patella, as the medial parapatellar approach splits and detaches a portion of the quadriceps from the patella [ 19 ]. To overcome this issue, some authors have described the utilization of a subvastus approach in these cases [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%